The Effect of Subtenons Lidocaine on Emergence Agitation after General Anesthesia in Pediatric Strabismus Surgery - L, Agolli.; B, Shuteriqi. (European Scientific Journal, ESJ, 2016)
Objectives: To study the effect of subtenon lidocaine injection at the end of intervention on the post-operative emergence agitation in pediatric strabismus surgery under general anesthesia with sevofluran. Material: We studied 191 children patients undergoing muscle surgery for strabismus from 2-6 years old. Children were (prospectively) randomized to one of the four groups. These groups include: A –Group Sevofluran fentanyl; B –Group sevoflurane fentanyl, Subtenon lidocaine injection; C – Group Propofol, fentanyl, sevofluran; and D – Group Propofol, fentanyl, Sevoflurane, Subtenon lidocaine injection. In the beginning of the induction of anesthesia, children received dexametasone and metoclopropamide. At the end of the surgery, children received either lidocaine (2%) or normal saline (1ml) into the subtenons space. This was conducted on the recovery room using five scoring scale. These scale include: 1- the child makes eye contact, 2- Purposeful response after repeated stimuli, 3 – the child is aware of the surrounding environment, 4- severe restlessness, and 5 – The child is inconsolable. The degree of emergence agitation was observed. Furthermore, the score 4 and 5 was considered as an emergence agitation. Results: There are no differences regarding age and weight. The incidence of emergence agitation was significantly lower in the groups which were receiving subtenon lidocaine compared with saline group injections (p< 0.05). Conclusions: A lidocaine injection into subtenon space reduces the emergence agitation after general anesthesia in pediatric strabismus surgery.